The Driving effect of industrial upgrading on new-type urbanization in Zhejiang Province - Gong, Junxi; Xu, Liya (Journal of Theory and Practice of Management Science, 2024)
The process of urbanization is supported by the economic foundation and accompanied by the upgrading of industrial structure. At present, the new-type urbanization of Zhejiang is in the stage of rapid development, and the upgrading of industrial structure is continuously and stably advanced and rational. Urban and rural development and urban construction are gradually moving towards a higher level. Therefore, it is of great significance to explore the driving effect of industrial upgrading on the new-type urbanization in Zhejiang Province for studying how to further promote the new-type urbanization process in China. Based on the analysis of industrial structure upgrading and urbanization in Zhejiang Province, this paper adopts the entropy weighting method to comprehensively evaluate the new-type urbanization level of each city in Zhejiang Province. Using panel data from 2009 to 2018, empirical analysis is made on the influencing factors of new-type urbanization level score of each city in Zhejiang Province. The influence of industrial structure upgrading index and other factors on the new-type urbanization level in Zhejiang province is obtained, which provides reference for Zhejiang and other regions to guide the industrial upgrading and improve the new-type urbanization development level.